The public university facing the XXI century - García, Leticia Sesento (Universidad Autónoma de Tamaulipas, 2019)
This essay is a reflection on the role of public higher education institutions facing the ravages of the 21st century. The current era is characterized by a marked uncertainty in all areas of life; the productive sectors of the country ask for innovations in universities, the pedagogical methods of formation of the future graduates of the public universities require revision, an evaluation of the connection between the labor market and the university is indispensable, besides the need to forge subjects trained to propose innovations in the chaotic, changing and new social environment. It is important that universities enter a process of reflection in their work be fore the transformations of the 21st century. When analyzing the scenrios in front of a state of the art technology, one perceives an atmosphere where the only thing that remains urgent to specify is to what extent these transformations impact as university professionals. The university is, for many students, possibility and a real hope of projecting themselves as moraland productive subjects.